EFEKTIVITAS HUMAN AND PUBLIC RELATION DALAM MEMBANGUN NILAI KOMUNIKASI LINTAS BUDAYA - Wayan Supada (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Every human being in his activities and interactions is always required to build relationships between one another. Relationships formed between humans are a combination of different individuals, ethnicities, cultures, religions. This condition requires self-adjustment skills to create a common perception in relationships that are built between humans. Humans in their existence are manifestations of beings who are required to always fulfill their needs, and this need is a competitive world reality demand. To realize that existence, humans try to initiate social reality so that they do not fall short of inability in the form of communication. In its application, human life is always faced with various phenomena of plurality in the form of skin color, ethnic plurality, religious plurality, and plurality of languages. With plurality it is often the trigger for conflict. To bridge the gap, various types of accommodation are needed that can bring these differences together so that there is understanding and recognition of the existence of a culture with adequate human relations and public relations capabilities. The better and more effective the pattern of managing this relationship, the better it will be in mediating the cross-cultural relations that occur so as to produce a shared value that is built.Keywords: Human Relation, Public Relation, Cross Culture, Communication Value